Transport and mental sciences in the territory of Al_Shash in Transoxiana 248 _ 447 AH / 862 _ 1055 AD - رندة عباس; محمد شاهين (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
With the establishment of the Abbasid Caliphate in the year 132 AH / 750 AD, the country beyond the river acquired an lslamic character, and economic life advanced in it, including agriculture, industry and trade From the scientific side, the region witnessed a civilized renaissance, especiallyin the region Al-Shash, (Today, Tashkent belongs to the State of Uzbekistan) but the political changes in it and the change of the system of government from to decentralized Abbasid led to the emergence of independent states from the Abbasid Caliphate that worked to support transportation (Hadith, interpretation and jurisprudence) and mental (lt depends on the mind of logic, theology philosophy) sciences to serve their goals, aspirations and the nature of their establishmen ln addition to the nature of the Al-Shash region, which is the last of the last of the jihadist the of against China and the Eastern Turks